Alternative pre-mRNA splicing in mammalian nervous system - Yap, Karen Lin Choo (2014)
Alternative pre-mRNA splicing provides a potent post-transcriptional mechanism for diversifying the transcriptome and regulating gene expression levels. Polypyrimidine tract-binding protein (Ptbp1) is a global regulator of alternative splicing affecting approximately a quater of the neuron-specific splicing events. Ptbp1 is expressed at high level in multiple cell types but down-regulated in neurons by brain-enriched microRNA miR-124. Many previous studies have examined Ptbp1-mediated regulation of cassette exons, internal exons that can be alternatively included or skipped. Here I describe two additional Ptbp1 functions.